The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1136/bjsports-2012-091855
|View full text |Cite
|
Sign up to set email alerts
|

Sports participation in non-compaction cardiomyopathy: a systematic review

Abstract: Non-compaction cardiomyopathy (NCCM) is typified by deep invaginations of the myocardium and is caused by an arrest of normal myocardial morphogenesis. NCCM was once considered rare, but is now widely recognised owing to frequent use of advanced imaging techniques. NCCM can also be detected when competitive athletes undergo preparticipation screening for cardiac disease or when being evaluated for cardiac symptoms. It is not clear how athletes with NCCM should be managed. We searched PubMed and Google for arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…175 The clinical diagnosis is currently reliant on three proposed echocardiographic criteria and are based on the demonstration of high non-compacted to compacted ratio within the LV myocardium. 173,174,177 Advances in tissue harmonics and image resolution in echocardiography have coincided with increased reports of features consistent with LVNC in patients with heart failure, 176 as well as in low-risk cohorts including sickle cell patients 178 and athletes, [179][180][181][182][183][184] particularly those of African/Afro-Caribbean origin. A study of over a 1000 asymptomatic athletes demonstrated that 18% exhibited increased LV trabeculations and 8% fulfilled echocardiographic criteria for LVNC, more commonly in black athletes.…”
Section: Left Ventricular Non-compactionmentioning
confidence: 99%
“…175 The clinical diagnosis is currently reliant on three proposed echocardiographic criteria and are based on the demonstration of high non-compacted to compacted ratio within the LV myocardium. 173,174,177 Advances in tissue harmonics and image resolution in echocardiography have coincided with increased reports of features consistent with LVNC in patients with heart failure, 176 as well as in low-risk cohorts including sickle cell patients 178 and athletes, [179][180][181][182][183][184] particularly those of African/Afro-Caribbean origin. A study of over a 1000 asymptomatic athletes demonstrated that 18% exhibited increased LV trabeculations and 8% fulfilled echocardiographic criteria for LVNC, more commonly in black athletes.…”
Section: Left Ventricular Non-compactionmentioning
confidence: 99%
“…Neither the extent to which physical training can alter non-compacted cardiomyopathy nor the prevalence of non-compacted LV morphology among healthy athletes have been determined. 151 , 152 Since forensic reports of SD in young athletes do not include non-compacted cardiomyopathy as a possible cause, it is not possible to apply risk stratification strategies for new patients with this disease.…”
Section: Individuals With Cardiomyopathies and Myocarditismentioning
confidence: 99%
“…The electrocardiogram (ECG) in LVNC is abnormal in up to 87% of cases but variable, with no definitive criteria. The most common ECG finding in athletes with LVNC is LVH by voltage criteria [68], with other arrhythmias detected on Holter or stress testing, all non-specific findings. LGE if present is supportive of myopathy and relates to adverse clinical features, but both athletes and LVNC may have no LGE so sensitivity is low [69].…”
Section: Left Ventricular Non-compactionmentioning
confidence: 99%